Player and Referee Roles Held Jointly: The Effect of State Ownership on China’s Regulatory Enforcement Against Fraud - Hou, Wenxuan (Journal of business ethics, 2010)
This article examines the impact of the prevailing state ownership in the Chinese stock market on corporate governance and the financial regulatory system, respectively, as the internal and external monitoring mechanisms to deter corporate fraud and protect investors. In line with the literature that state ownership exaggerates the agency problem, we find that the retained state ownership in privatised firms increases the incidence of regulatory enforcements against fraud. For the state-owned enterprises (SOEs), however, larger state ownership is associated with a lower incidence of enforcement actions. This is attributed to the mutual political affiliation of the fraudulent SOEs and the regulatory commission. A new regulation “Solutions for Listed Firm Checks” promulgated in March 2001 has mitigated this effect by empowering the regulatory commission to increase the severity of regulatory conditions. Our evidence confirms the improvement in the regulatory environment and investor protection in the Chinese stock market brought about by the regulatory reform and development.